Evaluation of Crack resistance and Adhesive Energy of AlCrN and Ag doped a-C Films deposited on Chrome Nitrided 316 LVM Stainless Steel. (31st October 2022) - Patnaik, Lokeswar; Maity, Saikat Ranjan; Kumar, Sunil
ABSTRACT: The present study characterises AlCrN and Ag doped a-C (a-C:Ag) biocompatible coatings for their nanomechanical, scratch, cracking behaviour, fracture toughness, and adhesion energy on chrome nitrided (CrN) medical grade 316 LVM stainless steel. The mechanical properties of the coatings are correlated with their structural make-up using XRD analysis. The results demonstrated superior behaviour of AlCrN compared to a-C:Ag coating in terms of high hardness and elastic modulus of the former. Owing to the inability of Ag to form carbide with carbon in a-C network contributed to discontinuity in the carbon structure resulting in compromised hardness and elastic modulus of the a-C:Ag coating. Further, a lower Hc 3 /Ec 2 ratio, relatively higher plasticity, and higher compressive stress of the AlCrN coating facilitated absorption of indentation load by virtue of plastic deformation, thus demonstrating less severe radial cracks and more pile-up induced circumferential cracks. The a-C:Ag coating predominantly suffered severe radial cracks attributed to easy debonding of immiscible Ag-C network. Thanks to the superior surface quality of a-C:Ag coating, it registered higher L c1 in the microscratch test; nonetheless, owing to the improved compressive stress, mechanical properties, and fracture toughness, AlCrN coating registered higher critical stress of coating failure and adhesion energy.